Q: Is -(x 1 to -x 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x3 + x2 - x - 1 = x2(x+1) - 1(x+1) =(x+1)(x2-1) = (x+1)(x+1)(x-1)

(x - 1)/x = x/x - 1/x = 1 - 1/x

(x - 1)(x - 1)(x - 1) - (x + 1)(x + 1)(x + 1)

Note that x² - 1 can be written as: x² + x - x - 1 Then, factor-by-group the expression to get: x(x + 1) - (x + 1) = (x - 1)(x + 1) Hence, x2 - 1 = (x + 1)(x - 1)

0

Related questions

1 to the power of 40 can be expanded to be: 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 X 1 Which would equal ..... 1

1 - x/(x2 + x) = 1 - x/[x(x+1)] = 1 - 1/(x+1) = (x+1)/(x+1) - 1/(x+1) = x/(x + 1)

120 = 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 = 1 The number one to the power of any non-negative integer is 1.

X+1=X=X+1

1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 = 19

-1 x -1 x -1 -x -x -1 -2x - 1

cos x / (1-sin x) = cos x (1 + sin x) / (1 - sin x) (1 + sin x) = cos x (1 + sin x) / (1 - sin2x) = cos x (1 + sin x) / cos2 x = (1 + sin x) / cos x = sec x + tan xcos x / (1-sin x) = cos x (1 + sin x) / (1 - sin x) (1 + sin x) = cos x (1 + sin x) / (1 - sin2x) = cos x (1 + sin x) / cos2 x = (1 + sin x) / cos x = sec x + tan xcos x / (1-sin x) = cos x (1 + sin x) / (1 - sin x) (1 + sin x) = cos x (1 + sin x) / (1 - sin2x) = cos x (1 + sin x) / cos2 x = (1 + sin x) / cos x = sec x + tan xcos x / (1-sin x) = cos x (1 + sin x) / (1 - sin x) (1 + sin x) = cos x (1 + sin x) / (1 - sin2x) = cos x (1 + sin x) / cos2 x = (1 + sin x) / cos x = sec x + tan x

x3 + x2 - x - 1 = x2(x+1) - 1(x+1) =(x+1)(x2-1) = (x+1)(x+1)(x-1)

(X^2 - 1)/(x-1) = (X+1)(X-1)/(X-1) = X+1

(x - 1)/x = x/x - 1/x = 1 - 1/x

x3 + 1 = x3 + x2 - x2 - x + x + 1 = x2(x + 1) - x(x + 1) +1(x + 1) = (x + 1)(x2 - x + 1)

d/dx (X - 1)x = (X - 1)x ln(X - 1) * x = X(X- 1)x ln(X - 1) -------------------------